Multi-target regulatory mechanisms and clinical assessment of natural products for insomnia: a review - Ma, Dongchuan; Yang, Hao; Zhao, Maoyuan; Luo, Zhaoliang; Teng, Renyi; Huang, Xiaofei; Liu, Tingting; Lv, Shangbin; Wang, Mingyu (Frontiers in Pharmacology, 2026)
BackgroundInsomnia, a prevalent sleep disorder, adversely impacts patients’ quality of life and imposes significant burdens on both physical and mental health. While conventional insomnia therapies remain widely utilized, they exhibit persistent safety limitations, including risks of dependence and cognitive impairment. Natural products have garnered increasing scientific interest owing to their favorable safety profiles and demonstrated therapeutic efficacy. This comprehensive review critically examines contemporary advances in understanding the mechanistic actions of natural products against insomnia and their supporting clinical evidence, with the objective of synthesizing their pharmacological mechanisms, clinical effectiveness, and safety evaluations.MethodsThis systematic review retrieved relevant literature through comprehensive searches of four core biomedical databases (ScienceDirect, PubMed, Ovid MEDLINE, and Web of Science), encompassing peer-reviewed articles published between January 2020 and August 2025. The retrieval strategy focuses on identifying original research papers concerning the treatment of insomnia using purified natural products and traditional Chinese medicine compound formulations.ResultsNatural products demonstrate significant therapeutic efficacy against insomnia through multi-target mechanisms, including: modulation of GABAergic neurotransmission, regulation of orexinergic signaling pathways, attenuation of inflammatory responses and oxidative stress, restructuring gut microbiota composition, and normalization of core circadian regulators (notably CLOCK/BMAL1 complexes). Critically, clinical evidence confirms these natural products treatment outcomes with favorable safety profiles in insomnia management.ConclusionThis review critically evaluates contemporary advances in botanical therapeutics for insomnia management, synthesizing evidence to inform evidence-based clinical translation and facilitate the development of novel pharmacotherapeutic strategies.